The Resilience of Junior High School Students in the Online Learning - Herul Wahyudin; Nandang Rusmana; Nandang Budiman (Psychocentrum Review, 2022)
This research was driven by the COVID-19 pandemic condition which caused face-to-face learning switched into learning from home or online. This raises various learning problems. To be able to deal with learning problems that arise from online learning, students need resilience. This implies that resilience is an important thing for students to have. The purpose of this study is to describe the resilience of students andexamine the differences between male and female students. The research design used a survey. The sample in this study was junior high school students (JHS) on the island of Java, amounting to 490 people. The sampling technique used Accidental Sampling. The data analysis used descriptive analysis and comparative analysis with a support from JASP software. The results showed that female students' resilience was higher than that of male students. The results of hypothesis testing indicates that there is a difference between male students’ resilience and female students’